(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
This study was conducted to determine the chemical andmicrobiological characteristics of traditional braided cheese (mudaffara)sold in Khartoum market, Sudan. Fifty four samples were collected fromthree different areas and subjected to chemical analysis (fat, protein, TS,ash, acidity) and microbiological examination (total viable bacteria,coliform bacteria, proteolytic bacteria, lipolytic bacteria, yeasts andmoulds counts). Results showed that batch number significantly affectedthe chemical components of cheese, while area from which samples werecollected did not. Fifty-five percent of samples had fat content of 26-37%, while 51% had low protein content (7-10%), 83% of samples hadtotal solids content of 55-70%, 70% of samples had ash content of 3-5.99%, and 39% were highly acidic (1.0-1.5%). Microbiologicalpopulations examined were high in batch B except for yeasts and mouldswhich were high in batch A. The area from which sampling was done didnot significantly affect the microbial quality of cheese.Microbiologically, samples were highly contaminated as shown in TVBC,where 89% of samples had Log 7.5-9.5 cfu/g, 89% had coliform count ofLog 2.0-2.80 cfu/g, 72% had proteolytic bacteria count of Log 2.0-3.0cfu/g, 65% had lipolytic bacteria count of Log 2.0-2.50 cfu/g and 91%had yeasts and moulds count of Log 2.0-3.80 cfu/g.